Characterization of a thyroid hormone receptor expressed in human kidney and other tissues. - Nakai, A (1988)
A cDNA encoding a specific form of thyroid hormone receptor expressed in human liver, kidney, placenta, and brain was isolated from a human kidney library. Identical clones were found in human placenta and HepG2 cDNA libraries. The cDNA encodes a 490-amino acid protein (Mr, 54,824). When expressed and translated in vitro, the protein product binds triiodothyronine with Ka of 2.3 X 10(9) M-1. This protein, designated human thyroid hormone receptor type alpha 2 (hTR alpha 2), has the same domain structure as other members of the v-erbA-related superfamily of receptor genes. It is similar to thyroid hormone receptor type alpha described in chicken and rat and less similar to human thyroid hormone receptor type beta (formerly referred to as c-erbA beta) from placenta. However, it is distinguished from these receptors by an extension of the C-terminal hormone binding domain making it 80 amino acids longer than rat thyroid hormone receptor type alpha 1 [Thompson, C.C., Weinberger, C., Lebo, R. & Evans, R. M. (1987) Science 237, 1610-1614]. Different sizes of mRNA found in liver (2.5 kilobases) and kidney (2 kilobases) suggest there may be tissue-specific processing of the primary transcript of this gene. Identification of human thyroid hormone receptor type alpha 2 indicates that two or more forms of thyroid hormone receptor exist in human tissues and may explain the normal variation in thyroid hormone responsiveness of various organs and the selective tissue abnormalities found in the thyroid hormone resistance syndromes.